1972
DOI: 10.1136/thx.27.4.468
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal tumours in Iceland 1956-70

Abstract: Seventeen histologically proved cases of primary mediastinal tumours were diagnosed in Iceland in 1956-70, during which period the average population was 180,000. Sixteen of these cases, seen at the Department of Thoracic Surgery, Landspitalinn, Iceland, are analysed.The patients' ages ranged from 1 to 59 years; 6 were males and 10 were females. Their symptoms are described. The commonest histological types were cysts (312%) followed by lesions of lymphatic origin (25%); 62-5% of the tumours were benign and 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Members of the genus are widely distributed, being found primarily in temperate regions. The genus contains approximately 55 species (Kirk et al 2008), which have been reported previously from Eastern Africa (Demoulin and Dring 1975), Finland (Haeggstrom 1997), Iceland (Hallgrimsson 1988), India (Sharma et al 2007), Japan (Yoshie et al 2004;Miwa and Kasuya 2009), Mexico (Calonge et al 2004), North America (Coker and Couch 1928;Bates et al 2009), northern Europe (Larsson et al 2009), Pakistan (Ahmad 1952;Ahmad et al 1997), Panama (Gube and Piepenbring 2009), South Africa (Bottomley 1948;Devilliers et al 1989), and South America (Suarez and Wright 1994;Baseia 2005;Trierveiler-Pereira et al 2010). Four species, B. bovistoides (Cooke & Massee) S. Ahmad, B. concinna S. Ahmad, B. lycoperdoides (Cooke) S. Ahmad, and B. plumbea Pers., have been reported previously from Pakistan (Ahmad 1952;Ahmad et al 1997).…”
Section: Introductionmentioning
confidence: 92%
“…Members of the genus are widely distributed, being found primarily in temperate regions. The genus contains approximately 55 species (Kirk et al 2008), which have been reported previously from Eastern Africa (Demoulin and Dring 1975), Finland (Haeggstrom 1997), Iceland (Hallgrimsson 1988), India (Sharma et al 2007), Japan (Yoshie et al 2004;Miwa and Kasuya 2009), Mexico (Calonge et al 2004), North America (Coker and Couch 1928;Bates et al 2009), northern Europe (Larsson et al 2009), Pakistan (Ahmad 1952;Ahmad et al 1997), Panama (Gube and Piepenbring 2009), South Africa (Bottomley 1948;Devilliers et al 1989), and South America (Suarez and Wright 1994;Baseia 2005;Trierveiler-Pereira et al 2010). Four species, B. bovistoides (Cooke & Massee) S. Ahmad, B. concinna S. Ahmad, B. lycoperdoides (Cooke) S. Ahmad, and B. plumbea Pers., have been reported previously from Pakistan (Ahmad 1952;Ahmad et al 1997).…”
Section: Introductionmentioning
confidence: 92%
“…The increasing accessibility of mediastinal structures to the surgeon, as the result of improving surgical techniques, has stimulated interest in neoplasms of this region. In consequence of this and the improved methods of diagnosis, more of these neoplasms have recently been reported by Boyd and Midell (1968), Wychulis, Payne, Clagett, and Woolner (1971), Benjamin, McCormack, Effler, and Groves (1972), La Franchi and Fonkalsrud (1973), and Hallgrimsson (1972).…”
mentioning
confidence: 93%